The Impact of Technological Innovation on Energy Consumption in OECD Economies: the role of Outward Foreign Direct Investment and International Trade Openness - Osabuohien-Irabor, Osarumwense; Drapkin, Igor Mikhailovich (International Journal of Energy Economics and Policy, 2022)
Over the last few years, empirical evidence has revealed that technological innovation plays a significant impact in reducing energy consumption and mitigation of carbon emission. But to achieve technological progress toward energy consumption sustainability, depend on several other factors. To this end, this study examines the role of outward foreign direct investment and international trade openness in innovation-energy nexus for 24 OECD countries for the period 1996-2015. To address econometric issues such as cross-sectional dependence, endogeneity, heterogeneity in the panel estimation process, this study employs the Cross-Sectionally Augmented autoregressive Distributed Lags (CS-ARDL), Augmented Mean Group estimator (AMG), and the System Generalized Methods of Moments (SYS-GMM) techniques. Finding reveals that the moderating effects of outward FDI and trade openness in the indirect relationship between technological innovation and energy demand exhibits an inverted U-shape curve. Specifically, this study finds that the impact of technological innovation on energy consumption via reverse technology spillover effect from outward FDI reinforces OECD countries toward energy-saving environmental sustainability both in the short-run and long-run. Furthermore, the joint impact of technological innovation and trade openness on energy demand is negative and statistically significant in the short and long run. This strengthens the efficiency of technologically innovative capabilities of OECD countries to effectively reduce energy consumption. These results are robust to different specifications and consistent across the various estimators, with sets of policy implication discussed.